2005
DOI: 10.1590/s0102-86502005000500011
|View full text |Cite
|
Sign up to set email alerts
|

Apendicite aguda isquêmica em coelhos: novo modelo com estudo histopatológico

Abstract: Apendicite aguda isquêmica em coelhos: novo modelo com estudo histopatológico ABSTRACT Purpose:To evaluate partial or total ischemia, through ligature with an unabsorbed thread of vessels from the vermiform appendix of rabbits, as well as the mechanical obstruction, through ligature with an unabsorbed thread at the basis of the vermiform appendix, at 1 cm from the cecum, of the acute appendicitis disease. To evaluate the histology of the appendix ( normal and affected ). To study the bacterium flora resident … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…An experimental study has shown that E coli is the most common bacterium found in the abdominal effusion during induced septic appendicitis (Nunes and Silva 2005). Based on current knowledge, it is difficult to determine whether bacterial growth in appendicitis is caused by the appendicitis itself or secondary to the dysbiosis caused by the appendicitis (Di Girolamo and others 2022).…”
Section: Which Treatment To Choose?mentioning
confidence: 99%
“…An experimental study has shown that E coli is the most common bacterium found in the abdominal effusion during induced septic appendicitis (Nunes and Silva 2005). Based on current knowledge, it is difficult to determine whether bacterial growth in appendicitis is caused by the appendicitis itself or secondary to the dysbiosis caused by the appendicitis (Di Girolamo and others 2022).…”
Section: Which Treatment To Choose?mentioning
confidence: 99%